FROM THE HISTORY OF NATIONAL PORTRAIT ART OF UZBEKISTAN - Alijon TURDALIEV, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides information about the initial formation factors of the national portrait art of Uzbekistan and the first portraits created in the national spirit. The works of the great painter K. Behzod, Mahmud Muzahib, Murad and Nadir Samarkandi are discussed.